Apolipoprotein L Expression Correlates with Neutrophil Cell Death in Critically Ill Patients. Issue 1 (January 2017) - Akl, Israa; Lelubre, Christophe; Uzureau, Pierrick; Piagnerelli, Michael; Biston, Patrick; Rousseau, Alexandre; Badran, Bassam; Fayyad-Kazan, Hussein; Ezedine, Mohammad; Vincent, Jean-Louis; Boudjeltia, Karim Zouaoui; Vanhamme, Luc
Abstract : Supplemental Digital Content is available in the text Abstract : ABSTRACT: Delayed neutrophil apoptosis has been demonstrated in sepsis and may contribute to organ damage. It has recently been proposed that apolipoprotein L (ApoL) may be involved in programmed cell death, but the expression and functions of ApoLs in leukocytes (especially neutrophils) during sepsis and other inflammatory conditions are currently unknown. In this prospective observational study in a 36-bed university hospital medicosurgical intensive care unit (ICU), we included 78 adult ICU patients with (n = 41) or without (n = 37) sepsis and 47 healthy volunteers. We analyzed ApoL mRNA expression using quantitative polymerase chain reaction in whole blood leukocytes and protein expression in CD15 + isolated neutrophils using Western blotting. Neutrophil apoptosis was assessed using the APO-BRDU method. Apolipoprotein L mRNA was downregulated in whole blood leukocytes and neutrophils in ICU patients compared with in healthy volunteers, and this effect translated at the protein level as indicated by Western blot analysis of neutrophils. There was a negative correlation between ApoL expression in neutrophils and C-reactive protein levels and a positive correlation between the number of apoptotic neutrophils and mRNA levels of ApoL1 and ApoL2. The degree of neutrophil apoptosis in critically ill patients is therefore correlated with modified expression profiles of ApoLs.